Hromadná otrava agrochemikálií - Volf, K; Hanus, V (Soudni lekarstvi, 1984)
A person showed signs of cholinesterase blockade after having a cup of coffee. Authors succeeded in proving an insecticide Lannate 90 WS in coffee grounds by mass spectrometry and thin-layer chromatography . The compound was later found in a table located in the building where intoxication had occurred and more persons had suffered from a sudden disease with similar signs previously.
Keywords: Czechoslovakia; Disease Outbreaks; lidé; Food Contamination; analýza potravin; kontaminace potravin; Humans; Československo; epidemický výskyt choroby; Food Analysis